“Is your eye evil because I am good?” On a Possible Reaction to Goodness - Draguła, Andrzej (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
In the parables of the workers in the vineyard and of the lost son, Jesus shows the relationship between goodness/forgiveness and justice. The protagonists of the two parables: the workers of the first hour as well as the elder son were expecting justice, while the vineyard owner and the father of the lost son showed goodness which rises above justice. This attitude triggers off “evil eye” of those whose sense of justice is disturbed. Whilst the Old Testament assumed the “eye for eye” rule as the fundamental social strategy, Jesus changes into the strategy of “do to others as you would have them do to you”. History shows that justice which is not counterbalanced by goodness, mercy, and forgiveness may deform into revenge, retaliation, vengeance. Although justice is still the basic norm of the society, it is goodness that should dominate in individual relations, even if it causes a negative reaction of those who construe goodness as injustice (trans. Agnieszka Piskozub-Piwosz)